Elaborasi Kreatif Multimedia Flip Book untuk Pengemasan Informasi, Promosi dan Edukasi pada Digital Library - Zurweni Zurweni; Dewi Iriani; Agus Salim (Departement of Mathematics Education, 2024)
The paradigm of the current global era, if viewed from the perspective of users, has been a change from the previous pattern where libraries only waited for users, so now libraries must be promoted to users (promote service to users). This research aims to obtain a new look regarding information packaging as well as promotion of Jambi University Library services using the creative Flip Book application through an elaboration process presented digitally online and offline. The creations carried out are combining images, writing with color and additional media so that it is more attractive to entrepreneurship-based readers. This research is Research & Development in the field of multimedia development for promotion and information, with Flip Book Builder, using the ASSURE Multimedia Model ID. This research makes a contribution to the Jambi University Library service system through more attractive online promotional displays and higher quality content. This results in increasing user/community recognition of the Jambi University Library Unit which is also an effort to realize UNJA's vision as a World class Entrepreneurship University based on Agro-Industry and the Environment.So far, library packaging and promotion in digital form and online displays have not been available at the Jambi University Library Unit.